(Invited) Nanostructured Rocksalt-Based Positive Electrode Materials for Rechargeable Li/Na Batteries - Yabuuchi, Naoaki (Meeting abstracts (Electrochemical Society), 2020)
In the past decade, lithium-enriched compounds, Li 2 MO 3 (M = Mn 4+, Ru 4+ etc .), have been extensively studied for high-capacity positive electrode materials of lithium batteries. Although the origin of high reversible capacities was a debatable subject for a long time, recently it has been evidenced that charge compensation is partly achieved by solid-state redox of non-metal anions, i.e ., oxide ions (anionic redox), coupled with redox reaction of transition metal ions (cationic redox), which is the basic theory used for classical lithium/sodium insertion materials. Recently, many cation-disordered rocksalt oxides have been proposed as a new series of electrode materials, which utilize reversible anionic redox. Nevertheless, insufficient electrode kinetics for the cation-disordered rocksalt system limits its use for practical applications. One simple strategy is to synthesize nanosized materials, which overcomes a problem of electrode kinetics (for electrons, holes and ions), and indeed electrode kinetics is significantly improved through nanosizing even for a non-lithium-excess and stoichiometric system. 1) Moreover, Nanosized Li/Na-excess oxides also deliver large reversible capacities even at room temperature, 2, 3) which shows much better electrode kinetics compared with as-prepared submicrometer-sized samples. From these findings, we discuss the advantages/disadvantages of “nanostructured” rocksalt-based electrode materialsto develop high energy Li/Na-ion batteries in the future. References Sato et al ., and N. Yabuuchi., Journal of Materials Chemistry A , 6 , 13943 (2018). Kobayashi et al ., and N. Yabuuchi, Small , 15 , 1902462 (6 pages) (2019). Kobayashi et al ., and N. Yabuuchi, Materials Today , in-press, DOI: 10.1016/j.mattod.2020.03.002